Consumer mortgage information search and information disclosures practices in Malaysia - Thi, Lip Sam; Tan, Sek-Choo; Kosim, Zunarni; Ahmad Zawawi, Suryati (2013)
The objective of the study is to examine consumers’ mortgage information search in deciding the choice of mortgage provider.The housing loan taken by Malaysian household has contributed about 45% of the total household debt.This implies that buying a house is the single, most expensive and major decision that any household has undertaken. Moreover, determining mortgage choices is complex for potential house buyers as mortgage market in Malaysia is exacerbated by various mortgage packages offer by conventional, Islamic financial institutions and non- financial institutions.Previous studies provided evidence that buyers must consider many factors before they derived at their most desirable mortgage package. Findings from this study revealed that housing developers and mortgage lenders are the most sought after medium by mortgage consumers when they search for mortgage information. Top four criteria perceived as critical by mortgage consumers are loan tenure, monthly repayment amount, interest rate (or profit rate in the case of Islamic financing) and margin of financing.The findings also showed there is fair disclosure of information to mortgage consumers in Malaysia.